2008
DOI: 10.1016/j.jcin.2008.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Stent Grafting of Dissected Descending Aorta in Patients With Marfan's Syndrome

Abstract: Endovascular stent grafting of the dissected DTA is feasible in selected Marfan patients with low mortality and morbidity rates. Nevertheless, the rate of primary and secondary endoleak is high. Close imaging surveillance is crucial to detect secondary aortic complications and to assess long-term results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 66 publications
(43 citation statements)
references
References 21 publications
3
39
0
1
Order By: Relevance
“…Marcheix et al showed a similarly high primary treatment failure rate to our study, with primary endoleak occurring in 33% of patients, secondary endoleak occurring in another 33%, and an additional two patients requiring subsequent intervention for unrelated aortic pathology. 12 There was a 60% mortality in the primary endoleak group, and eight of 15 patients in this study required subsequent operative intervention, mirroring the results in our series.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Marcheix et al showed a similarly high primary treatment failure rate to our study, with primary endoleak occurring in 33% of patients, secondary endoleak occurring in another 33%, and an additional two patients requiring subsequent intervention for unrelated aortic pathology. 12 There was a 60% mortality in the primary endoleak group, and eight of 15 patients in this study required subsequent operative intervention, mirroring the results in our series.…”
Section: Discussionsupporting
confidence: 84%
“…However, the use of endovascular therapy for patients with Marfan syndrome is still controversial and has been reported only in small series and isolated case reports. [6][7][8][9][10][11][12] To our knowledge, our analysis represents the largest series published to date. In this series, TEVAR was performed in 15 patients and EVAR in one patient.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Cardiac auscultation demonstrated a systolic ejection click and crisp mechanical second sound. The patient did not M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 4 have orbital hypertelorism or bifid uvula. Medications included losartan, simvastatin, aspirin and warfarin.…”
Section: History and Physical Examinationmentioning
confidence: 92%
“…Current observational evidence suggests that TEVAR improves survival in complicated distal dissection [ 21 ]. In patients with connective tissue disease, however, remodeling is achieved less frequently and endovascular strategies are discouraged or considered as bridging to definitive open repair [ 36 ].…”
Section: Interventional Managementmentioning
confidence: 99%